Problematika Penerjemahan Al-Qur′an dalam Bahasa Indonesia - Nashruddin Baidan (IAIN Surakarta, 2017)
The study of the translation of Qur'an in Indonesian is intended to map the translation of Qur'an in Indonesian. Based on the literature review, we found some problematic Indonesian translation of Qur'an. Translation of the Qur'an as a holy book should not be mistaken. If this happens, then the function of Qur'an as a guide turns into a heresy. The translation must be done with precision and accuracy. This paper intends to examine the problematic translation of the Qur'an into Indonesian in terms of context, culture, and conditions surrounding it. Any criticism of the translation in this study is based on original documents using rational, objective and argumentative thought. After a critical analysis of several translations in Basmalah, al-Ikhlas and al-Ma'un, it finds that the translation of the Indonesian Qur'an does not fully follow the rules and procedures of translation. In general, the translation process is done literally, not contextually. On the other hand, the subjective thinking in translation seems more dominant than rational, objective and argumentative thinking.